(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Temporal expressions play a crucial role in shaping communicative meaning across languages. Beyond their grammatical function of locating events in time, they perform important pragmatic functions such as managing discourse, expressing politeness, structuring interaction, and negotiating social relationships. This article examines how temporal forms—tense markers, adverbials, metaphoric time expressions, and context-dependent temporal cues—are pragmatically employed by speakers to achieve communicative goals. Drawing on insights from pragmatics, discourse analysis, and cognitive linguistics, the paper analyzes direct and indirect temporal references, the role of deixis, the influence of cultural norms, and the strategic use of temporal vagueness. The study demonstrates that temporal expressions constitute a rich pragmatic resource that reflects speakers’ intentions, interpersonal strategies, and cultural assumptions. It concludes that understanding temporal pragmatics is essential for a comprehensive view of meaning-making in natural language communication.